INTERNATIONAL MOBILE TELECOMMUNICATION-2000 (IMT-2000) - Dulbert, Biatna; W., Denny; A., Dhandy (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
International Mobile Telecommunication-2000 (IMT-2000) is a third-generation mobile communication system. It has been established as an international standard to realize advanced services and also overcome the performance limitations of the telephone and data communication services that are based on existing second-generation mobile communication systems (i.e., Personal Digital Cellular (PDC), CDMAOne, and Global Systems for Mobile communications (GSM). This research outlines the services recommended in IMT-2000 and describes the base station systems, switching systems, and various servers of the IMT-2000 network architecture.